Optimisasi Analisis Pelaksanan Pelaporan Pasien Menggunakan Sistem Informasi Rumah Sakit( SIRS) Online di Rumah Sakit Sentra Medika Sanggau Tahun 2023 - Sardi, Aditiya; Wahyudi, Wahyudi (Jurnal Riset Sistem dan Teknologi Informasi, 2025)
Hospital Information System is the collection, processing and presentation of hospital data throughout Indonesia. The purpose of this study was to determine the percentage of patients for the period 2022-2023 and to determine the factors that influence the implementation of patient reporting using the Online Hospital Information System (SIRS) at Sanggau Medika Center Hospital. This type of research is descriptive with a qualitative approach that aims to determine the implementation of patient reporting using the online Hospital Information System (SIRS). The results of this study are seen from the human factor, the number of officers is still lacking with the number of officers only two people. Method, there is no standard operating procedure regarding patient reporting using the Online Hospital Information System (SIRS). Machines, networks that are experiencing problems. Material, the absence of a hospital management information system has a direct impact on the effectiveness and efficiency of staff work. In conclusion, the utilization of the Online Hospital Information System (SIRS) application at Sanggau Medika Center Hospital is quite good but still not optimal, because the number of officers is still limited and the available facilities cannot fully support the utilization of the Online Hospital Information System (SIRS) in patient reporting.